Spontaneous Flexor Tendon Rupture Due to Atraumatic Chronic Carpal Instability - Miranda, B. H.; Cerovac, S. (Journal of Wrist Surgery, 2014)
Background Spontaneous flexor tendon rupture is considered to be invariably associated with previous hand/wrist injury or systemic disease such as rheumatoid arthritis.Case Description A 54-year-old man presented with a 4-month history of mild ulnar wrist pain and spontaneous left little finger flexion loss in the absence of distant/recent trauma and systemic arthropathy. Surgical exploration confirmed a zone IV left little finger flexor digitorum profundus (FDP5) attritional rupture (100%), ring finger flexor digitorum profundus (FDP4) attenuation (40%) and a disrupted lunotriquetral ligament and volar-ulnar wrist capsule. Volar subluxation of the narrowed carpal tunnel resulted in flexor tendon attrition against the hamate hook. A side-to-side tendon transfer was performed along with a lunotriquetral ligament repair and temporary Kirschner wire fixation. At 6 months the patient had full active, synchronous flexion of the ring and little fingers and reduced wrist pain.Literature Review Traumatic flexor tendon ruptures have been reported following distal radius/hamate hook fractures, from carpal bone osteophytes, accessory carpal bones and intraosseous ganglia. Attritional ruptures caused by chronic, degenerative carpal pathology are less common.Clinical Relevance This case highlights an unusual cause of flexor tendon rupture due to chronic carpal instability.
Keywords: attrition rupture; flexor tendon; hamate; lunate subluxation; carpal instability